Macrophage migration inhibitory factor and oral cancer - França, Cristiane M.; Batista, Aline C.; Borra, Ricardo C.; Ventiades-Flores, Jose A.; Mendonça, Elismauro F.; Deana, Alessandro M.; Mesquita-Ferrari, Raquel A.; de Natali Caly, Decio; de Mello Rode, Sigmar [UNESP]; Faria, Miriam R. (Wiley, 2013)
Background: Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine with pro-inflammatory functions and involved in tumorigenesis. The aim of this study was to evaluate the expression and localization of the macrophage MIF in oral squamous carcinoma (OSC). In addition, the relationship between MIF expression and clinicopathological parameters such as survival data, tobacco use, alcohol habits, TNM stage, tumor graduation, and peritumoral inflammatory infiltrate were evaluated. Methods: Using immunohistochemistry, expression and localization of MIF was detected in 44 specimens of OSC. The absolute number and relative proportions of MIF-positive cells detected were also determined separately for tumor parenchyma vs. stroma. All counts were determined from 10 consecutive high-power fields using an integration graticule. Moreover, some parameters were analyzed separately for lip and intra-oral cancers. Results: Migration inhibitory factor-positive cells were observed in both the tumor parenchyma and in inflammatory cells of all specimens. In contrast, MIF expression was not detected in tumoral nests associated with poorly differentiated tumors. In specimens of lip cancer, a greater number of MIF-positive stromal immune cells were detected than in intra-oral cancer specimens (Mann-Whitney test, P = 0.049). Conclusions: Oral squamous carcinoma cells consistently express MIF independent of their location. Lip tumors presented more MIF-positive peritumoral inflammatory cells, similar to control, suggesting that immunological differences in leukocyte activation exist between in lip and intra-oral cancers. © 2012 John Wiley & Sons A/S.
Keywords: Immunohistochemistry; Macrophage migration inhibitory factor; Mouth neoplasms; Oral cancer; macrophage migration inhibition factor; adult; cancer grading; cancer localization; cancer staging; cancer survival; cellular distribution; clinical article; clinical feature; female; human; human tissue; immunocompetent cell; immunohistochemistry; immunolocalization; inflammatory cell; inflammatory infiltrate; lip cancer; male; mouth cancer; parenchyma; priority journal; protein expression; stroma cell; tumor differentiation